Writing Ability Improvement Through Student Teams Achievement Divisions at Pirayanawin Klonghin Wittaya School - Mustika, Nurika (Universitas Muhammadiyah Jember, 2016)
The aims of this research is to find out how Student Teams-Achievement Divisions (STAD) can improve students’ descriptive writing ability of the third grade students at Pirayanawin Klonghin Wittaya School, Thailand in the 2014/2015 academic year. The design of this research is classroom action research (CAR). The subject of the research is the third grade of Pirayanawin Klonghin Wittaya School in the 2014/2015 academic year that consists of 33 students. The observation used writing test as primary data and observation checklist. STAD improved the students descriptive writing ability in two cycles from the percentage of students scored ≥ 63,was 56.6% in cycle 1 to 80% in cycle 2 and from M= 62.2 in cycle 1 to M= 72 in cycle 2. Based on the research result, it can be concluded that STAD (Student Achievement Divisions) is able to improve students’ descriptive writing ability by having heterogeneous teams in terms of ability and gender that make them easy in generating their ideas and able to have peer tutoring.Keywords: writing ability, STAD (students teams achievement divisions)